MICROBIOLOGICAL ACTIVITY OF SOIL. REPRODUCTIVE ACTIVITY AND IMPORTANCE OF TUBERCLE BACILLI (Conferencea, 2022)
The article provides information on the microbiological activity of the soil, the types of microorganisms in the soil, their role in increasing soil fertility, symbiotic relationship.